MONITORING OF BACTERIAL AGENTS - ETIOLOGICAL FACTORS OF MASS GASTRO-INTESTINAL DISEASES OF YOUNG POULTRY - V. A. Chkhenkeli; A. V. Anisimova; N. A. Goryaeva (Acta Biomedica Scientifica, 2012)
The work presents the results of epizootological monitoring of mass gastro-intestinal diseases of young poultry in the Irkutsk Region. As a result of the poultry sickness rate analysis covering the period, of 2006-2010 the following nosological units have been distinguished: colibacteriosis (37,3 %), salmonellosis (25,4 %), pasteurellosis (19,8 %), spirochetosis (14,4 %), staphylococcus diseases (2,9 %), infectiouslaryngotracheitis (0,2 %). The results of the monitoring research, indicated that gastro-intestinal diseases are caused, by a wide range of opportunistic pathogenic microflora agents. However, these bacteria groups are mostly represented by microorganisms Enterobacteriaceae family of Escherichia and Salmonella types. The research established not only wide diversity of the distinguished serological colon bacillus and. salmonella varieties, but also fluctuations in their proportion in the common structure of the distinguished culture in the examined time interval.